The Change of The Magnitude of The Electric Field Vector (EyE0) in The Ionosphere in The Magnetic Equator Through - Yeşil, Ayşe Nazan; Özcan, Onur; İnç, Mustafa; Sağır, Selcuk; Kurt, Kadri; Tsamalashvili, L.v.; Kaladze, D.t. (My University, 2021)
The seasonal changes of (Ey/E0), which was obtained from the WKB (Wentzel, Kramers, Brillouin) solution, for (- 300N; 300S geographic latitudes and (390, 410, 450, 500, 550 and 600 Km) altitudes in the equatorial anomaly region were investigated. (Ey/E0) ratio takes minimum value in latitudes, where the electron density is at maximum levels and takes maximum value in places where the electron density is at minimum levels, respectively. It is possible to say that in places where the electron density is at maximum, the wave transfers energy to the medium, otherwise it receives energy from the medium.
Keywords: Refractive index; ionosphere; wkb; equatorial anomaly